1998
DOI: 10.1007/s004210050342
|View full text |Cite
|
Sign up to set email alerts
|

Failure to obtain a unique threshold on the blood lactate concentration curve during exercise

Abstract: The purpose of this study was to compare various methods and criteria used to identify the anaerobic threshold (AT), and to correlate the AT obtained with each other and with running performance. Furthermore, a number of additional points throughout the entire range of lactate concentrations [La-] were obtained and correlated with performance. A group of 19 runners [mean age 33.7 (SD 9.6) years, height 173 (SD 6.3) cm, body mass 68.3 (SD 5.4) kg, maximal O2 Uptake (VO2max) 55.2 (SD 5.9) ml x kg(-1) x min(-1)] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 30 publications
(54 reference statements)
2
32
0
4
Order By: Relevance
“…Based on these observations, we conclude that the two repeated sprint training sessions were effort matched. However, heart rate values demonstrated a "steady state" condition during repeated 20 m sprints at 90% intensity, and corresponding lactate values were below what has been considered "lactate threshold intensity" (BLa -between 2.5 and 4.0 mmol·L -1 ) in endurance training (Tokmakidis & Pilianidis, 1998). In contrast, repeated sprinting at maximal intensity induced a progressive increase in heart rate, as well as BLa -at or above the typical lactate threshold range described for endurance athletes.…”
Section: Effort Matched Sprint Trainingmentioning
confidence: 83%
“…Based on these observations, we conclude that the two repeated sprint training sessions were effort matched. However, heart rate values demonstrated a "steady state" condition during repeated 20 m sprints at 90% intensity, and corresponding lactate values were below what has been considered "lactate threshold intensity" (BLa -between 2.5 and 4.0 mmol·L -1 ) in endurance training (Tokmakidis & Pilianidis, 1998). In contrast, repeated sprinting at maximal intensity induced a progressive increase in heart rate, as well as BLa -at or above the typical lactate threshold range described for endurance athletes.…”
Section: Effort Matched Sprint Trainingmentioning
confidence: 83%
“…Therefore, LA at LT is apparently lower than LA as used to date, and 0.1 mmol/l above resting level would be appropriate. In older individuals, previously described procedures for determining LT that evaluate accelerate increase of LA based on the frequently blood sampling [Beaver et al, (1985) ; Tokmakidis et al, (1998)] was sometime cause the lower accuracy and/or the determination rate, because of the diffi culties in blood sampling above LT [Belman and Gaesser, (1992)]. In this research, similarly, of the 105 subjects who were given the graded exercise test, we were able to obtain suffi cient LA to determine LT in only about half, or 52 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…B l o o d l a c t a t e c o n c e n t r a t i o n ( L A ) d u r i n g submaximal exercise is closely related to aerobic capacity, especially, lactate threshold (LT) and OBLA (Onset of Blood Lactate Accumulation) are indicators of aerobic capacity better or at least no worse than V ・ of aerobic capacity better or at least no worse than ・ of aerobic capacity better or at least no worse than O 2 max [Yoshida et al, (1987) ; Tokmakidis et al, (1998)]. Because LT in particular can be measured in light to moderate submaximal exercise, it has possibilities for safe and accurate evaluation, in older people.…”
Section: Introductionmentioning
confidence: 99%
“…The critical power has been shown to be a useful fitness measure in trained cyclists (Smith et al 1999) and is related to the maximal lactate steady state (Jones and Carter 2000). Furthermore, it has been shown that any rightward shift of the power output -blood lactate relation reflects improved lactate threshold regardless how the lactate threshold have been determined (Tokmakidis et al 1998). This agrees with the finding that six different methods of determine the lactate threshold all showed significant correlations with 1-h time trial cycling performance (Bishop et al 1998).…”
Section: Paragraph Numbermentioning
confidence: 99%